Evaluasi Pelaksanaan Kebijakan Merdeka Belajar pada Satuan Pendidikan Non-Formal - I’zaati, Lailatul; Rahma, Mia Aisyah; Bashith, Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Non-formal education is a planned and systematic educational curriculum that is implemented independently by the government and the community in achieving learning goals. The purpose of this evaluation discussion is to improve the independence of non-formal education units by optimizing secondary data obtained from various relevant references collected through the development of documents and documentation matrices of norms, standards, procedures, and activities to provide recommendations. regarding study guidelines. The stages of data reduction, data presentation, and conclusion drawing are analyzed. To ensure freedom of learning with a quality learning process in non-formal education units, the learning process also requires quality teaching resources. What is important here is that the government pays attention to universities that train private teachers. Therefore, alternative recommendations that need to be considered by the government include (1) freedom of learning policy, (2) quality teacher policy.